Consumer access to clozapine in Australia: how does this compare to New Zealand and the United Kingdom? - Knowles SA; McMillan SS; Wheeler AJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Clozapine is an antipsychotic medication used in treatment resistant schizophrenia. However, clozapine is associated with a significant adverse effect profile and extensive monitoring is required to optimise consumer safety. Traditionally, clozapine can only be prescribed by a psychiatrist and dispensed at a hospital or hospital affiliated pharmacy in Australia. These restrictions could result in significant treatment burden for consumers taking clozapine. Objective: To identify (1) the different models of supply that exist for people living in the community taking clozapine in Australia and compare to those in New Zealand and the United Kingdom, and (2) explore how these supply models may impact on consumer burden from the perspective of professionals involved in the supply of clozapine. Method: Key informants were interviewed (n=8) from Australia, New Zealand and the United Kingdom regarding how consumers, who lived in the community, accessed clozapine. Data were analysed and led to the development of four clozapine supply models. These four models were further validated by an online survey of a wider sample (n=30). Data were analysed thematically and via simple descriptive statistics. Results: Clozapine supply varied depending on location. A secondary care model was utilised in the United Kingdom compared to a community based (primary care) model in New Zealand; Australia utilised a mixture of both secondary and primary care. A key theme from all study participants was that community pharmacy should be utilised to dispense clozapine to consumers living in the community, provided adequate training and safeguards are in place. It was noted that the utilisation of community pharmacies could improve access and flexibility, thereby reducing treatment burden for these consumers. Conclusion: There are predominately two models for supply of clozapine to consumers living in the community in Australia, New Zealand and the United Kingdom. One model utilises secondary care facilities and the other community services. Community pharmacy is ideally placed to increase access to clozapine for consumers living in the community, provided appropriate training and support is given to pharmacists providing this professional service.